Sustained heterologous gene expression in pancreatic islet organoids using adeno-associated virus serotype 8 - Voznesenskaya, Anna; Berggren, Per-Olof; Ilegems, Erwin (Frontiers in Bioengineering and Biotechnology, 2023)
Genetic modification of pancreatic islet organoids, assembled in vitro prior to transplantation is an emerging alternative to direct in vivo genetic manipulations for a number of clinical and research applications. We have previously shown that dispersion of islet cells followed by reaggregation into islet organoids, or pseudoislets, allows for efficient transduction with viral vectors, while maintaining physiological functions of native islets. Among viruses currently used for genetic manipulations, adeno-associated viruses (AAVs) have the most attractive safety profile making them suitable for gene therapy applications. Studies reporting on pseudoislet transduction with AAVs are, however, lacking. Here, we have characterized in detail the performance of AAV serotype 8 in transduction of islet cells during pseudoislet formation in comparison with human adenovirus type 5 (AdV5). We have assessed such parameters as transduction efficiency, expression kinetics, and endocrine cell tropism of AAV8 alone or in combination with AdV5. Data provided within our study may serve as a reference point for future functional studies using AAVs for gene transfer to islet cell organoids and will facilitate further development of engineered pseudoislets of superior quality suitable for clinical transplantation.